2019
DOI: 10.1002/celc.201901224
|View full text |Cite
|
Sign up to set email alerts
|

The Key Role of Water Activity for the Operating Behavior and Dynamics of Oxygen Depolarized Cathodes

Abstract: Advanced chlor‐alkali electrolysis with oxygen depolarized cathodes (ODC) requires 30 % less electrical energy than conventional hydrogen‐evolution‐based technology. Herein, we confirm that the activities of hydroxide and water govern the ODC performance and its dynamics. Experimental characterization of ODC under varying mass transfer conditions on the liquid side reveals large differences in the polarization curves as well as in potential step responses of the electrodes. Under convective transport in the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 40 publications
2
32
0
Order By: Relevance
“…Although recent simulation work on ORR at catalysts in gas diffusion electrodes provides high current densities, being in good agreement with experimental results, even when assuming continuous thin electrolyte films in the range of 25–300 nm covering the catalyst particles and without considering uptake control, [51] this does not contradict the results reported here. In fact, for the same kind of electrode it was reported that the gas‐liquid interface is by far more complex than a homogenously thin film, rather being characterized by a high density of micro‐droplets, as was revealed by operando X‐Ray imaging [52] .…”
Section: Discussionsupporting
confidence: 90%
“…Although recent simulation work on ORR at catalysts in gas diffusion electrodes provides high current densities, being in good agreement with experimental results, even when assuming continuous thin electrolyte films in the range of 25–300 nm covering the catalyst particles and without considering uptake control, [51] this does not contradict the results reported here. In fact, for the same kind of electrode it was reported that the gas‐liquid interface is by far more complex than a homogenously thin film, rather being characterized by a high density of micro‐droplets, as was revealed by operando X‐Ray imaging [52] .…”
Section: Discussionsupporting
confidence: 90%
“…Based on these findings, the authors draw the conclusion that a high electrode performance requires a good mass transport of water and hydroxide ions in the liquid phase as well as an extended gas‐liquid interface. The strong influence of water and ion transport on the performance of the electrodes was also confirmed experimentally . As a consequence, it is essential to achieve an optimized electrolyte boundary e. g. by a variation of the hydrophobic part of the GDE.…”
Section: Introductionmentioning
confidence: 64%
“…Röhe et al [44] established a dynamic three-phase model of advanced chlor-alkali electrolysis porous ODC, which proved that water transport, especially that of hydroxide ions in the liquid electrolyte, is the overall limiting factor. The oxygen concentration is rapidly consumed near the gas-liquid interface [45]. Considering the non-ideal behavior of highly concentrated water, the water activity coefficient largely depends on ion concentration [46].…”
Section: Odc Electrode Structure and Working Principlementioning
confidence: 99%